VALIDITAS DAN PRAKTIKALITAS LEMBAR KERJA ELEKTRONIK MATERI BENTUK ALJABAR KELAS VII SMP - Sumargiyani, Sumargiyani; Tsani, Shafwa (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2024)
One of the learning objectives is to obtain optimal student learning outcomes. To achieve this goal, it is necessary to carry out learning activities that are supported by adequate learning tools. The aim of this research is to develop student worksheets in electronic form that are valid and practical. Carrying out research in class VII of SMP Muhammaduyah 6 Yogyakarta in the odd semester 2023/2024. Research using the ADDIE stage (analysis, design, development, implementation and evaluation). The electronic LKPD that was developed involved two material experts and media experts as validators, as well as one class of students to test the practicality of the instrument. The data obtained was analyzed based on valid and practical categories by calculating based on a percentage formula. Based on the assessment of material validity, it is categorized as very valid with an average score of 82.89%, media validity is categorized as very valid with an average score of 94.48% and the practicality of electronic LKPD is categorized as very practical with an average score of 83.91%. So that the electronic LKPD created is suitable for use in learning algebra material for class VII middle school.